Promotion of proper christian religious education : a strategy to wards achieving active participation of the laity in the church's pasto ral ministry : case study of Ndeeba parish, Kampala - Ssentamu, George William (Kampala, 2013)
Unpublished thesis (MARTS) - Makerere University, 2013.
Includes bibliographical references.
Keywords: Christian religious education -- Ndeeba parish -- Uganda; Pastoral theology -- Catholic church -- Ndeeba parish -- Uganda